Interleukin 1 family dysregulation in serum and peritoneal fluid of ovarian cancer patients – potential clinical implications - Stępień, Sebastian; Smycz-Kubańska, Marta; Morawiec, Maria-Laura; Seweryn, Kamil Radosław; Mielczarek-Palacz, Aleksandra (Frontiers in Oncology, 2026)
In the pathomechanism of ovarian cancer development, an important role is attributed to the chronic inflammatory process. Still, despite numerous studies, it has not been fully elucidated how immune inflammatory processes influence the development of ovarian cancer. Immune system mediators – cytokines, especially interleukin-1 family members – are involved in interactions between cancer cells and immune cells. Therefore, learning about the relationship between the coexistence of inflammatory and neoplastic processes in ovarian cancer involving these molecules may contribute to a better understanding of the importance of the studied parameters in the pathogenesis of cancer, which may also translate into improved clinical efficacy. In the present study, for the first time, the analysis between the levels of all 11 members of the IL-1 family (IL-1α, IL-1β, IL-18, IL-33, IL-36α, IL-36β, IL-36γ, IL-37, IL-1Ra, IL-36Ra, IL-38) has been made, which belong to the main inflammatory cytokines, in both serum and peritoneal fluid of ovarian cancer patients. The analysis revealed differences in the concentration of individual members of IL-1 in both serum and peritoneal fluid between the study group and the reference group, as well as between G1, G2 and G3 stages of ovarian cancer, and differences in the ratio between the interleukins studied. The results indicate the involvement of the studied parameters in the pathomechanism of ovarian cancer development and the regulation of stimulation of inflammation accompanying ovarian cancer. Disruption of the secretion of secreted cytokines in serum and peritoneal fluid in patients with ovarian cancer may lead to their pro-inflammatory activation, indicating that modulation of cytokines of the IL-1 family may affect the course of the inflammatory process that accompanies the development of cancer. The observed perturbations involving the cytokines studied may represent one of the more important immune mechanisms that promote the development of this cancer, indicating the need for new complex therapies targeting a wide variety of immune response mechanisms, but this requires further, more advanced research.